The Epistles and the Book of Revelation [electronic resource]. - Peck, E. J. (Edmund James), 1850-1924.; Bilby, J. (Julian) (London : British and Foreign Bible Society, 1908)
Cover title: Eskimo Epistles & Revelation. "Changed from the Labrador dialect and written in syllabic character by the Rev. E.J. Peck, Assisted by Mr. J. Bilby." Electronic reproduction. Mode of access: Internet. 44